Nursing care for HIV/AIDS patients according to the Virginia Henderson model - Lizcano Ramírez , Jennifer; Ordoñez Delgado, Scarlet Jamileth; Zambrano Arteaga , Gema Magdalena; Chávez Arizala, Jenrry Fredy (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: the nursing professional plays the role of providing or assisting with care and needs. There are several theories or models that govern nursing care. Virginia Henderson introduces a holistic humanistic model that can be applied to special groups such as patients with HIV/AIDS. The objective of the research was to characterize nursing care for HIV/AIDS patients according to the Virginia Henderson model. Methods: a literature review was conducted, where 25 articles in Spanish and English were selected, published in the last five years on the subject, in databases such as: Scopus, Pbmed, Springer. Results: assuming the care of people with HIV/AIDS is opting for the care of an incurable and life-limiting condition. Nurses must assist the person in procedures or in their treatment and create a bond of therapeutic help; guaranteeing professional confidentiality of the diagnosis, focusing on addressing the pathology and opportunistic infections, providing the means that contribute to achieving patient independence; as well as preventing stigma and social rejection of the patient. Conclusions: care for patients with HIV/AIDS requires professionals prepared to guarantee the necessary care for this specialized group. The required psychological, physical and emotional support must be provided, avoiding rejection or overprotection of the position, seeking solutions by providing patients with humane treatment; preventing social stigma, rejection and demoralization